Pendidikan Etika dalam Pandangan Hamka: Relevansinya dalam Membentuk Akhlak Gen Z di Era Digital - Nurwahida; Fitry Anggraini; Abdurrahmansyah; Muhammad fauzi (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
The rapid development of information and communication technology presents complex moral challenges for Generation Z, such as value disorientation, weak role models, and negative social media influence. This study aims to examine Hamka’s concept of ethical education and its relevance for shaping Generation Z’s character in the digital era. Using a qualitative approach through library research, this study analyzes primary texts by Hamka, including Tasawuf Modern, Falsafah Hidup, and Lembaga Budi, supported by recent academic literature. The population includes Hamka’s main works and contemporary studies on ethics and digital generation challenges. Sampling follows purposive criteria based on thematic relevance. Data were analyzed using content analysis to interpret ethical values in Hamka’s writings within today’s character education context. The results indicate that core values such as honesty, responsibility, simplicity, sincerity, and self-control remain highly significant in addressing Generation Z’s moral issues. These values integrate well with Indonesia’s Merdeka Curriculum and the Pancasila Student Profile, providing practical guidance for educators and families. The study concludes that Hamka’s ethical philosophy offers a robust framework to foster noble character amid digital challenges. Future research should incorporate empirical data to evaluate the practical implementation of these values in educational settings.